2023
DOI: 10.3389/fimmu.2023.1230261
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Camrelizumab combined with gemcitabine and oxaliplatin in the treatment of advanced intrahepatic cholangiocarcinoma: a case report and literature review

Zhongyan Zhang,
Xin Wang,
Hehe Li
et al.

Abstract: Intrahepatic cholangiocarcinoma (ICC) is one of the most common invasive malignant tumors, with a 5-year survival rate of less than 5%. Currently, radical surgical resection is the preferred treatment for ICC. However, most patients are only diagnosed at an advanced stage and are therefore not eligible for surgery. Herein, we present a case of advanced ICC in which radical surgery was not possible due to tumor invasion of the second porta hepatis and right hepatic artery. Six treatment cycles with a gemcitabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies on the application of pembrolizumab for incurable cholangiocarcinoma in Phase I b and II trials have found that regardless of PD-L1 expression, it can effectively control 6%-13% of advanced bile duct cancers, with manageable toxicity (6).A real-world study based on Phase III clinical trial TOPAZ-1, incorporating durvalumab into the first-line chemotherapy regimen for cholangiocarcinoma, demonstrated a 20% reduction in the risk of death (HR=0.80, 95% CI: 0.66-0.97, P=0.021), confirming the efficacy and safety of durvalumab for cholangiocarcinoma patients (7). Subsequently, more studies and case reports on the application of other immune checkpoint inhibitors in cholangiocarcinoma have emerged, further bolstering the case for immunotherapy in cholangiocarcinoma (8)(9)(10)(11).Currently, the combination of durvalumab with gemcitabine and cisplatin is an option for first-line treatment of locally advanced or metastatic cholangiocarcinoma. However, further research is needed to verify the application of immune checkpoint inhibitors in cholangiocarcinoma and to identify prognostic risk factors for patients receiving immunotherapy.…”
Section: Introductionmentioning
confidence: 86%
“…Studies on the application of pembrolizumab for incurable cholangiocarcinoma in Phase I b and II trials have found that regardless of PD-L1 expression, it can effectively control 6%-13% of advanced bile duct cancers, with manageable toxicity (6).A real-world study based on Phase III clinical trial TOPAZ-1, incorporating durvalumab into the first-line chemotherapy regimen for cholangiocarcinoma, demonstrated a 20% reduction in the risk of death (HR=0.80, 95% CI: 0.66-0.97, P=0.021), confirming the efficacy and safety of durvalumab for cholangiocarcinoma patients (7). Subsequently, more studies and case reports on the application of other immune checkpoint inhibitors in cholangiocarcinoma have emerged, further bolstering the case for immunotherapy in cholangiocarcinoma (8)(9)(10)(11).Currently, the combination of durvalumab with gemcitabine and cisplatin is an option for first-line treatment of locally advanced or metastatic cholangiocarcinoma. However, further research is needed to verify the application of immune checkpoint inhibitors in cholangiocarcinoma and to identify prognostic risk factors for patients receiving immunotherapy.…”
Section: Introductionmentioning
confidence: 86%